PENGARUH LATIHAN PASSIMANIACS TERHADAP KETERAMPILAN PASSING PADA PEMAIN SEPAKBOLA SMA AN-NAAS PEKANBARU - Dwi Angraina; Ramadi '; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: From the observation of researchers in the field at SMA AN-NAAS players. There was some weaknesess that seem in training and competition soccer, that is infirmnity not optimal in passing. This could be seen when passing often do not fit on a friend team,as for the time of passing easily retrived by enemy. The purpose of this research is to know effect of a workout on the passing skills of the player’s SMA AN-NAAS Pekanbaru. The population in this research is 11 peoples by using the total sampling, so that the sample totaled were 11 peoples. Instruments in this research is passing test. Data were analyzed by using tes-t based on the test prodces tcount=8,533 with ttabel=1,812 and than be accepted, on alfa ( 0,05. It can be concluded that there are significan exercise passimaniacs to the passing skills on the soccer player’s SMA AN-NAAS PekanbaruKeywords: passimaniacs, passing